The way of the Wesleys : a short introduction - Tyson, John R. (Grand Rapids, Mich. : William B. Eerdmans, 2014)
The Wesley brothers -- John (1703-1791) and Charles (1707-1788) -- are famous as the cofounders of the Wesleyan tradition and the Methodist family of churches. Their impact and legacy have been huge : what began as the excited outpouring of their conversion experiences grew into a transatlantic revival and became a vibrant and significant theological tradition. But what exactly did they believe and teach? In this book John Tyson, an acknowledged authority on Methodist studies, offers a helpful introduction to the main teachings and practices of both John and Charles Wesley. The first book to show how Charles, the younger and lesser-known brother, contributed in particular to Wesleyan theology, The Way of the Wesleys takes readers through main theological points thematically. Tyson also includes suggestions for further reading and questions for reflection at the end of each chapter. Lavishly documented from the Wesleys' own writings, this engaging, accessible book shows why the Wesleys remain relevant to the faith journey of Christians today.
We to the sacred standard fly: the Bible -- Purge the foul inbred leprosy: sin -- My chains fell off: the new birth -- Pure and spotless let us be: holiness -- His pity no exception makes: grace -- The promised paraclete is given: the Holy Spirit -- Risen with healing in his wings: Jesus Christ -- He breaks the power of canceled sin: Christian perfection -- An interest in my Savior's blood: the atonement -- One glorious God in persons three: the Trinity -- I in thy temple wait: the means of grace -- A soul-transporting feast: the Lord's Supper -- Our loving labor: life in the world -- All united in they name: an ecumenical spirit -- Conclusion: The way of the Wesleys.
Includes bibliographical references (p. 193-195) and indexes.
Print version record.
Keywords: Wesley, John, -- 1703-1791.; Wesley, Charles, -- 1707-1788.; Methodist Church -- Doctrines; Wesley, Charles, -- 1707-1788.; Wesley, John, -- 1703-1791.; Methodist Church -- Doctrines; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Methodist; Electronic books